The Pro-Environmental Behavior Task: A laboratory measure of actual pro-environmental behavior. (April 2018) - Lange, Florian; Steinke, Alexander; Dewitte, Siegfried
Abstract: To address the limitations of self-report measures, we developed the Pro-Environmental Behavior Task (PEBT) as a computerized paradigm for the assessment of actual pro-environmental behavior under controlled laboratory conditions. On each PEBT trial, participants can either choose the faster car option, which causes a series of lights to be illuminated, or they can save the associated energy by choosing the bicycle option at the expense of spending more time in the laboratory. In two pre-registered studies (both N = 120), we showed that the proportion of environmentally friendly PEBT choices is a valid and reliable measure of pro-environmental behavior. PEBT choices were consistent across trials, correlated to conceptually relevant variables, and sensitive to conceptually relevant manipulations. These effects were replicable and independent of the labelling of PEBT options. Our findings highlight the psychometric quality and utility of the PEBT as a paradigm that can open new avenues for research on pro-environmental behavior. Highlights: This paper introduces the Pro-Environmental Behavior Task (PEBT). PEBT choices lead to actual consequences for the individual and for the environment. Two pre-registered studies support the validity and reliability of the PEBT. PEBT choices are correlated to conceptually relevant self-report measures. PEBT choices are sensitive to the individual and environmental costs of the behavior.